Electrical characteristics of flash sintering: thermal runaway of Joule heating - Todd, R; Zapata-Solvas, E; Bonilla, R; Sneddon, T; Wilshaw, P (Elsevier, 2015)
Flash sintering occurs when an electric field is applied to a heated ceramic powder compact. At a critical combination of field and temperature, a power surge occurs (the "flash event") and sintering takes place in a few seconds. This paper investigates the possibility that this surge occurs by runaway Joule heating. The resistivity of 3YSZ was measured under the relevant conditions. To a good approximation, resistivity was found to be history-independent and to have the same temperature dependence before and after the flash event. These data were used to model the thermal and electrical response of 3YSZ to an applied electric field. All electrical characteristics of the flash event observed experimentally were predicted with a high degree of accuracy. It is concluded that the thermal and electric characteristics of flash sintering are a classical consequence of the negative temperature coefficient of resistivity leading to runaway Joule heating at constant voltage.